Whole-Exome Sequencing Reveals Recurrent but Heterogeneous Mutational Profiles in Sporadic WHO Grade 1 Meningiomas - González-Tablas, María; Prieto, Carlos; Arandia, Daniel; Jara-Acevedo, María; Otero, Álvaro; Pascual, Daniel; Ruíz, Laura; Álvarez-Twose, Iván; García-Montero, Andrés Celestino; Orfao, Alberto; Tabernero, María Dolores (Frontiers in Oncology, 2021)
Human WHO grade 1 meningiomas are generally considered benign tumors; despite this, they account for ≈50% of all recurrent meningiomas. Currently, limited data exists about the mutational profiles of grade 1 meningiomas and patient outcome. We investigated the genetic variants present in 32 WHO grade 1 meningiomas using whole exome sequencing, and correlated gene mutational profiles with tumor cytogenetics and patient outcome. Overall, WHO grade-1 meningiomas harbored numerous and heterogeneous genetic variants, which most frequently affected the NF2 (47%) gene and to a less extent the PNMA6A (22%), TIGD1 (16%), SMO (13%), PTEN (13%), CREG2 (9%), EEF1A1 (6%), POLR2A (6%), ARID1B (3%), and FAIM3 (3%) genes. Notably, nonsynonymous genetic variants of SMO and POLR2A were restricted to diploid meningiomas, whereas NF2 mutations were only found among tumors that showed -22/22q ̶ (with or without a complex karyotype). Based on NF2 mutations and tumor cytogenetics, four genetic profiles were defined with an impact on patient recurrence-free survival (RFS). These included: 1) two good-prognosis tumor subgroups -diploid meningiomas (n=9) and isolated -22/22q ̶ associated with NF2 mutation (n=7)- with RFS rates at 10y of 100%; and, 2) two subgroups of poor-prognosis meningiomas -isolated -22/22q ̶ without NF2 mutation (n=3) and tumors with complex karyotypes (n=11)- with a RFS rate at 10y of 48% (p=0.003). Our results point out the existence of recurrent but heterogeneous mutational profiles in WHO grade 1 meningiomas which have an impact on patient outcome.